Augmentation Therapy With Serotonin 5‐HT1A Receptor Partial Agonists on Cognitive Function in Depressive Disorders: A Systematic Review of Randomized Controlled Studies - Risa Yamada; Ayumu Wada; Andrew Stickley; Adrian Newman‐Tancredi; Tomiki Sumiyoshi (Neuropsychopharmacology Reports, 2025)
ABSTRACT Objective The use of serotonin 5‐HT1A receptor partial agonists (5‐HT1A‐PAs) as an add‐on therapy has been associated with the enhancement of attention/processing speed in patients with schizophrenia. Also, 5‐HT1A receptors have been shown to play a role in the pathophysiology of mood disorders. There is compelling evidence supporting that stimulation of 5‐HT1A receptors accelerates antidepressant effects. Accordingly, this systematic review examines the ability of adjunctive treatment with 5‐HT1A‐PAs to improve cognitive function in patients with depressive symptoms. Methods A literature search using PubMed, the Cochrane Library, and Web of Science databases was performed from 1987 to January 2024 to identify randomized controlled trials (RCTs) corresponding to the following inclusion criteria: (1) RCTs, (2) human studies; studies that (3) targeted patients with a psychiatric disorder (except for schizophrenia or schizoaffective disorder), (4) evaluated the effect of cognitive functions, (5) were written in English. Results From the 80 studies initially screened, three met the inclusion criteria. Two of these studies dealt with vascular depression while one focused on major depressive disorder (MDD). In MDD, combined treatment with buspirone and melatonin was more efficacious in ameliorating subjective cognitive disturbances compared to the use of buspirone alone or the use of a placebo. Likewise, the combination of escitalopram–tandospirone was more advantageous than escitalopram alone for improving executive function and verbal fluency in patients with vascular depression. Conclusions Further studies with novel 5‐HT1A receptor agonists are warranted to examine their potentially more robust benefits on cognitive performance in subjects suffering from mood deficits.